ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ANGKA KECUKUPAN ENERGI RUMAH TANGGA PETANI DI KABUPATEN KLATEN - Wahyu Adhi Saputro; Yuli Fidayani (Universitas Tidar, 2020)
The energy intake consumed by a person will affect the health of each individual. The energy adequacy figure for household consumption is also used as a reference for the value of family food security. The purpose of this study is to analyze the factors that affect the energy adequacy rate of farmer households in Klaten Regency. The location of the research was carried out deliberately in Klaten Regency because this area is a rice producer in Central Java. The samples used were farmers in the independent food village of Klaten Regency. This research uses descriptive analytical method with multiple linear regression analysis. The results showed that there are four variables that influence the energy adequacy rate, namely the education of the head of the farmer household, rice consumption, consumption of tempe and nutritional knowledge by the farm-housewife.Keywords: Consumption, Energy Adequacy Rate, Farmers